Ecosystems of Innovation: Factors of Social Innovation and its Role in Public Policies. Issue 4 (2nd October 2022) - Silva-Flores, Martha Leticia; Murillo, David
Abstract : This article seeks to advance knowledge of social innovation through understanding how public policy frameworks can both support and constrain its efficacy in an ever-changing world. In doing so, this article contributes to the framework for studying interventions related to innovation models that emerge from a multidisciplinary approach to interpreting ecosystems. The question this paper attempts to answer: how can we best mitigate and overcome challenges and obstacles posed to social innovation in growing ecosystems? To answer this, we examined empirical data from actors involved in social innovation projects from two distinct, growth-stage ecosystems: Guadalajara, Mexico and Barcelona, Spain. The analysis yields three key constraining factors that obstruct social innovation: 1) Lack of critical mass for social innovation. 2) Fragmentation of actors' efforts in the innovation ecosystem. 3) Lack of citizen participation. By synthesising both the existing literature and this paper's findings, we'll propose three strategies that address issues that growing ecosystems face in their efforts to implement social innovation. The first strategy refers to mechanisms that connect citizens to scientific knowledge. The second pertains to the construction of common frameworks of action by different actors. Finally, the third strategy highlights the importance of citizen participation in social innovation projects.